Photoconversion of carbon dioxide in zinc–copper–gallium layered double hydroxides: The kinetics to hydrogen carbonate and further to CO/methanol - Morikawa, Motoharu; Ahmed, Naveed; Yoshida, Yusuke; Izumi, Yasuo (Applied catalysis. B, Environmental, 2014)
•Electron diffusion was faster in the direction of double hydroxide layer.•CO2 was in equilibrium with HCO3 species for the reaction with hydroxy groups.•Interlayer spacing affected the CO2 diffusion into the interlayer reaction space.•The decomposition of HCO3 under light was enhanced by the addition of H2.•Photocatalytic conversion of CO2+H2 should be via HCO3 species to methanol/CO. Photocatalytic reaction mechanism for the conversion of CO2 into methanol and CO using layered double hydroxides (LDHs) consisting of Zn, Cu, and Ga was investigated. X-ray absorption fine structure was applied to determine the LDH site structures and to monitor the diffusion of photogenerated electrons to CuII sites. Electron diffusion to Cu sites was an order of magnitude faster in the direction of the cationic layers (580μmolh−1gcat−1) than in the perpendicular direction. According to Fourier-transform infrared spectroscopy, CO2 was in equilibrium with hydrogen carbonate (1629cm−1 for H13CO3) for the reaction with hydroxy group from the cationic layer or interlayer site and/or with interlayer water. The equilibrium reactions were faster for [Zn3Ga(OH)8]+2[Cu(OH)4]2−·mH2O (400–110μmolh−1gcat−1) than for [Zn1.5Cu1.5Ga(OH)8]+2(CO3)2−·mH2O. Furthermore, the reductive decomposition of hydrogen carbonate was suggested in H2 under UV–visible light, suggesting photocatalytic pathway to methanol/CO.